Employee Performance Allowance Effects on Human Resource Productivity and Welfare in Papua - Merry Susiani Samba; Hasan Basri Umar; Risky Novan Ngutra (Jurnal Pemberdayaan Ekonomi, 2026)
Purpose: This study examines the effect of the employee performance allowance, locally known as Tambahan Penghasilan Pegawai (TPP), on human resource productivity and employee welfare among civil servants at the Agency for Apparatus Resource Development or Balai Pengelolaan Sumber Daya Air (BPSDA) of Papua Province, and tests whether productivity mediates the relationship between the allowance and welfare. Research Methodology: A quantitative approach was applied to all 60 civil servants at BPSDA using a saturated sampling technique. Data were collected through a five-point Likert-scale questionnaire and analyzed with simple linear regression, path analysis, and the Sobel test using SPSS version 24.Results: The performance allowance had a positive and significant effect on productivity, but no significant direct effect on welfare. Productivity had a positive and significant effect on welfare, and productivity significantly mediated the relationship between the allowance and welfare, with the indirect effect exceeding the direct effect.Conclusions: The performance allowance improves employee welfare mainly through the channel of productivity rather than through a direct income effect.Limitations: The cross-sectional design, the single-institution sample, and reliance on perception data restrict generalizability. Contributions: The study offers empirical evidence for performance-based compensation policy in a remote provincial civil service and extends human capital and motivation theory to a Papuan public-sector setting.